The role of social media in gastronomy industry - Hegyesné Görgényi, Éva; Máté, Balázs; Vafaei, Seyyed Amir; Farkasné Fekete, Mária (Applied Studies in Agribusiness and Commerce, 2017)
Considering the rapidly changing business environment, staying competitive is a key issue and challenge for companies in the 21st century. The criteria of a company’s success and competitiveness is the changing behavior of the different economic actors and its influence. Through the information society came to the fore, the use of diverse information technology tools and methods has become a significant influence factor in terms of the entrepreneurs or company management and also the customers or other partners. Due to the rapid expansion of new technology developments, the role and importance of social media is continuously increasing. Also statistics show that one of the most regularly used IT tool is the social media and the different web 2.0 applications. The current study is intended to provide a better understanding how social media can emphasize the competitiveness of companies and format the consumer behavior in a special sector – the rapidly developing gastronomy industry. This paper presents an empirical research about the role of social media in the above mentioned industry based on the primary data which are gathered through a survey performed in Hungary. Beyond the empirical results presented, the paper also aims to provide some recommendations for research methodology – based on the international literature review and the Authors’ own experiences – both in gastronomy industry’s and customers’ point of view. Through the analysis the research hypotheses were examined and the most important correlations were identified between the survey results and the Authors’ initial supposition. JEL Code: D83, L83, M31, Z33